Innovation of Islamic Religious Education In The Digital Era - Isma Mufidah (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
In the current era of technology is the existence of learning innovation. Educators, especially Islamic religious educators, must make the best use of technological advances. Utilization of technology in the learning process both in the classroom and outside the classroom is a must so that the learning process is not stagnant and rigid. The internet as a learning innovation that is more modern, adaptive, and aligned with the independent learning curriculum is a learning medium that can be an alternative method of PAI learning. This can be in the form of e-learning or applications that facilitate the delivery of learning materials, so that the learning process is more interesting and not boring, so that it can improve Islamic education in Indonesia.